Prevalence of Insomnia among Medical Students - Mahwish Adnan, Muhammad Hassan Ali, Sadia Nikhet, Farhana Begum, Arfa Arshad, Bakht Khizar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency and prevalence of insomnia among medical students of sheikh Zayed hospital and medical college Study design: Cross sectional study. Place and Duration of Study: Study started from 1st September 2018 and lasted to 30th March 2019 and was carried out at Sheikh Zayed Medical College and Hospital (Rahim Yar Khan). Methodology: This study was done through a questionnaire (Athens Insomnia Scale (AIS). Sample of the study consisted in medical students who were chose by random sampling to check the prevalence of insomnia. 75 students were male and 60 were female. Similarly,14 students from third year, 93 from fourth year and 28 from final year of MBBS. Complete history record maintain in academic years, sleep hour, midday nap and common cause of sleep disturbance mention in the literature: age, gender, habitat, BMI, physical activity, smoking and socioeconomic status was taken from the participant. During the interview, psychological assessment done for psychiatric illness and other screening for medical issues. Results: Study was done on the sample size (N) of two hundred and sixty (260) medical students. Response rate was 90% for two hundred and fifty students (250). 101(40.4%) were male out of these 250 students, and 149(59.6) were female students. Maximum and minimum age of the students was 25 years and 18 years respectively and mean age of the respondents was 21.076±1. This scale Athens Insomnia Scale, 102 (40.8%) participants were found to be insomnic and 148(59.2%) are non-insomniac. Among 102 Insomniac students, 70 were females and 32 were males. So result indicates that insomnia is more common in females then males. Conclusion: Insomnia is very common in medical student’s .This study shows that prevalence of insomnia in medical students is high. While the severity of insomnia is greater in female medical students as compare to the male students. Practical Implication: In our system, proper assessment of such problems would help in developing policies and adjusting medical study curricula to boost the output of one of the most expensive professional degree courses. Keywords: Insomnia, Medical students, Athens Insomnia Scale, BMI,